Pengaruh Literasi Bencana Pesantren Tradisional dan Modern Terhadap Kesiapsiagaan Bencana - Suyanto; Enok Maryani; Iwan Setiawan (Jurnal Penelitian Pendidikan Geografi, 2023)
Disaster preparedness is a crucial capability that must be possessed by residents of Islamic boarding schools located in the Bandung City. One effort to develop disaster preparedness skills is by increasing disaster literacy skills among Islamic boarding school residents. This research aims to examine the influence of modern and traditional Islamic boarding school disaster literacy on disaster preparedness in Bandung City. This research used descriptive and survey methods with a sample of 360 students spread across several zones in the city of Bandung. The questionnaire instrument was distributed to all samples to be analyzed using correlation tests and t-tests. The research findings indicate that: 1) there is an influence of disaster literacy among traditional boarding school students on disaster preparedness, thus accepting H1 and rejecting H0; 2) there is an influence of disaster literacy among modern boarding school students on disaster preparedness, thus accepting H0 and rejecting H1. Based on these results, it can be concluded that both traditional and modern Islamic boarding school disaster literacy have an impact on disaster preparedness.